PEMANFAATAN STRATEGI ATM UNTUK MENINGKATKAN PERFORMA MEDIA SOSIAL UMKM CRAFTOTE - Lydia Irena; Steven Winata; Jhodi Triputra Wirjadi; Keisha Ong; Evelyn Jofani; Robin Untung (Jurnal Bakti Masyarakat Indonesia, 2026)
The rapid growth of social media platforms has transformed how small businesses build awareness and connect with audiences. TikTok and Instagram, as the most engaging platforms among Indonesian users, have become essential tools for micro, small, and medium enterprises (MSMEs) to expand their visibility. However, many local businesses still struggle to adapt their content strategies effectively. This paper presents a digital marketing training and implementation project conducted with Craftote, a café and gallery in West Jakarta promoting local handmade crafts. The project focused on applying the ATM method (Observe, Copy, Modify) as a creative framework to design and produce social media content that aligns with viral trends while maintaining Craftote’s sustainable and artistic identity. The team observed trending content on TikTok’s “For You Page,” replicated relevant formats, and modified them with original ideas to produce engaging videos. Through this hands-on implementation, Craftote’s TikTok views increased from 1,047 to more than 112,000, and Instagram reach grew by approximately 135%, with 79% of viewers being new audiences. Beyond numerical improvements, the project demonstrated how structured digital marketing training combined with creative adaptation could foster brand authenticity, improve engagement, and build stronger public awareness. This activity serves as a practical model for MSMEs seeking to integrate ethical creativity with social media strategy in order to achieve sustainable brand visibility. Pertumbuhan pesat media sosial telah mengubah cara pelaku usaha kecil membangun kesadaran merek dan menjalin hubungan dengan audiensnya. TikTok dan Instagram kini menjadi dua platform paling populer di Indonesia dan berperan penting dalam memperluas jangkauan UMKM. Namun, masih banyak pelaku usaha lokal yang kesulitan dalam mengelola strategi konten secara efektif. Makalah ini membahas kegiatan pelatihan dan implementasi digital marketing yang dilakukan bersama Craftote, sebuah café dan galeri di Jakarta Barat yang menampilkan kerajinan tangan lokal. Kegiatan ini menerapkan metode ATM (Amati, Tiru, Modifikasi) sebagai kerangka kreatif untuk merancang dan memproduksi konten media sosial yang mengikuti tren tanpa meninggalkan identitas merek Craftote yang berkelanjutan dan artistik. Tim mengamati tren di halaman For You Page (FYP) TikTok, meniru format yang relevan, dan memodifikasinya dengan ide orisinal untuk menghasilkan konten yang menarik. Melalui implementasi langsung, tayangan TikTok Craftote meningkat dari 1.047 menjadi lebih dari 112.000, sementara jangkauan Instagram naik sekitar 135% dengan 79% penonton baru. Lebih dari sekadar hasil statistik, kegiatan ini menunjukkan bahwa pelatihan digital marketing yang terarah dan adaptasi kreatif dapat memperkuat autentisitas merek, meningkatkan keterlibatan audiens, serta membangun kesadaran publik yang lebih luas. Kegiatan ini menjadi model praktis bagi UMKM lain dalam mengintegrasikan kreativitas etis dan strategi media sosial guna mencapai visibilitas merek yang berkelanjutan.